Divergent Biochemical Properties and Disparate Impact of Arrhythmogenic Calmodulin Mutations on Zebrafish Cardiac Function - Sahar I. Da'as (17128747) (2024)
Calmodulin (CaM) is a ubiquitous, small cytosolic calcium (Ca2+)‐binding sensor that plays a vital role in many cellular processes by binding and regulating the activity of over 300 protein targets. In cardiac muscle, CaM modulates directly or indirectly the activity of several proteins that play a key role in excitation‐contraction coupling (ECC), such as ryanodine receptor type 2 (RyR2), l‐type Ca2+ (Cav1.2), sodium (NaV1.5) and potassium (KV7.1) channels. Many recent clinical and genetic studies have reported a series of CaM mutations in patients with life‐threatening arrhythmogenic syndromes, such as long QT syndrome (LQTS) and catecholaminergic polymorphic ventricular tachycardia (CPVT). We recently showed that four arrhythmogenic CaM mutations (N98I, D132E, D134H, and Q136P) significantly reduce the binding of CaM to RyR2. Herein, we investigate in vivo functional effects of these CaM mutations on the normal zebrafish embryonic heart function by microinjecting complementary RNA corresponding to CaMN98I, CaMD132E, CaMD134H, and CaMQ136P mutants. Expression of CaMD132E and CaMD134H mutants results in significant reduction of the zebrafish heart rate, mimicking a severe form of human bradycardia, whereas expression of CaMQ136P results in an increased heart rate mimicking human ventricular tachycardia. Moreover, analysis of cardiac ventricular rhythm revealed that the CaMD132E and CaMN98I zebrafish groups display an irregular pattern of heart beating and increased amplitude in comparison to the control groups. Furthermore, circular dichroism spectroscopy experiments using recombinant CaM proteins reveals a decreased structural stability of the four mutants compared to the wild‐type CaM protein in the presence of Ca2+. Finally, Ca2+‐binding studies indicates that all CaM mutations display reduced CaM Ca2+‐binding affinities, with CaMD132E exhibiting the most prominent change. Our data suggest that CaM mutations can trigger different arrhythmogenic phenotypes through multiple and complex molecular mechanisms. Other Information Published in: Journal of Cellular Biochemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jcb.30619